Photo-based individual identification is more reliable than visible implant elastomer tags or toe-tipping in young agile frogs - Edina Nemesházi; Nikolett Ujhegyi; Zsanett Mikó; Andrea Kásler; Vera Lente; Veronika Bókony (PLoS ONE, 2026)
In amphibian capture-recapture studies, commonly used individual-identification methods include toe clipping as well as less invasive alternatives of varying cost. Yet, choosing the best method for a study is challenging, because both the reliability for identification and the severity of adverse effects of a given mark type can greatly vary between species as well as life stages. We compared the reliability of three identification methods in young agile frogs ( Rana dalmatina ): clipping a single phalanx, injecting visible-implant-elastomer (VIE) tags (one of six colours) under the skin, and photo-based identification using natural colouration. Individuals were regularly photographed from the start of metamorphosis onwards, and were marked by the other two methods soon after all of them finished metamorphosis. Subsequently, we checked mark retention by each method multiple times for more than a year. Photo-based identification was far more reliable than the other two methods: 100% identification success post-metamorphosis in all checking events within small housing groups, and 98% with computer-assisted identification across all housing groups. Post-metamorphic body colouration remained largely stable, and the major patterns were already present at metamorphosis. Based on VIE colour alone, we could correctly identify the animals in 77% of the checks. Green tags were the easiest to recognize. VIE often broke into smaller parts, and those were sometimes found only outside the originally tagged body part (15%) or not found at all (10%). VIE was better retained in the legs than in the arms. Dissection revealed that migrating VIE pieces can accumulate in the internal organs, especially the kidneys. The clipped toe tip was successfully recognized only in 41% of checks. We conclude that photo-based identification is superior to both VIE-tagging and toe tipping in young agile frogs, and this method should be preferred in future studies seeking a cost-efficient yet reliable identification method in this species.